2018
DOI: 10.1128/jvi.01999-17
|View full text |Cite
|
Sign up to set email alerts
|

Positive Regulation of Hepatitis E Virus Replication by MicroRNA-122

Abstract: The molecular mechanisms of liver pathology and clinical disease in hepatitis E virus (HEV) infection remain unclear. MicroRNAs (miRNAs) are known to modulate viral pathogenesis either by directly altering viral gene expression or by enhancing cellular antiviral responses. Given the importance of microRNA-122 (miR-122) in liver pathobiology, we investigated possible role of miR-122 in HEV infection. predictions using HEV genotype 1 (HEV-1), HEV-2, HEV-3, and HEV-4 sequences showed that the majority of genomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 39 publications
1
32
0
1
Order By: Relevance
“…While miR-122 was reduced in the post-treatment sample of the HEV/HCV co-infected patient, we did not observe statistically significant differences in our sample group comparisons. We do not know the reason for this, but one explanation could be that the conserved miR-122 target sequence was also described in HEV genomes and appeared to facilitate HEV replication, which is greatly reduced by the inhibition or depletion of miR-122 [50]. This might have skewed the comparisons in the infected samples.…”
Section: Pre-and Post-treatment Samples Of the Hev/hcv Co-infected Pamentioning
confidence: 99%
“…While miR-122 was reduced in the post-treatment sample of the HEV/HCV co-infected patient, we did not observe statistically significant differences in our sample group comparisons. We do not know the reason for this, but one explanation could be that the conserved miR-122 target sequence was also described in HEV genomes and appeared to facilitate HEV replication, which is greatly reduced by the inhibition or depletion of miR-122 [50]. This might have skewed the comparisons in the infected samples.…”
Section: Pre-and Post-treatment Samples Of the Hev/hcv Co-infected Pamentioning
confidence: 99%
“…This treatment indeed suppressed HCV replication [39]. In view of the in-vitro study reported very recently [31] and the results presented here in HE patients, it would be prudent to explore the utility of miR-122-LNA in the treatment of the disease. Further, if the findings in acute patients are confirmed in the chronic HE patients, LNAs can offer an attractive therapy.…”
Section: Discussionmentioning
confidence: 53%
“…One possibility could be requirement of physical binding of miR-122 during HEV replication leading to reduced serum levels irrespective of liver damage. Our in-vitro experiments did document binding of miR-122 to HEV genome enhancing HEV replication [31].…”
Section: Discussionmentioning
confidence: 61%
“…During viral infection, host innate immunity is blocked at an early stage, and our previous studies also suggested that activated type I IFN signalling was quickly suppressed after FHV-1 infection [13], but some miRNAs are still upregulated to enhance IFN signalling pathways [21,23]. More importantly, it has been reported that some microRNAs can also inhibit virus replication by targeting viral genomes directly [25,26]. Given the critical roles of miRNAs in regulating type I IFN signalling, it is unknown whether the host uses these miRNAs to restart the IFN signalling pathways upon FHV-1 infection.…”
Section: Introductionmentioning
confidence: 97%